2012
DOI: 10.1158/0008-5472.can-11-3001
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic Immunotherapy of Advanced Solid Tumors with a CD40L-Expressing Replicating Adenovirus: Assessment of Safety and Immunologic Responses in Patients

Abstract: The immunosuppressive environment of advanced tumors is a primary obstacle to the efficacy of immunostimulatory and vaccine approaches. Here, we report an approach to arm an oncolytic virus with CD40 ligand (CD40L) to stimulate beneficial immunologic responses in patients. A double-targeted chimeric adenovirus controlled by the hTERT promoter and expressing CD40L (CGTG-401) was constructed and nine patients with progressing advanced solid tumors refractory to standard therapies were treated intratumorally. No … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
108
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 119 publications
(111 citation statements)
references
References 50 publications
2
108
0
1
Order By: Relevance
“…6 However, previous work has also revealed the ability of CD40L to induce APC activation not only CD40 C but also in CD40 ¡ tumors, suggesting the potential use of virus for tumor immunotherapy regardless of CD40 status. 6,7,52 This is in accordance with our study in which Ad3-hTERT-CMV-hCD40L (Figs. 3C-E) as well as virally produced hCD40L (Figs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…6 However, previous work has also revealed the ability of CD40L to induce APC activation not only CD40 C but also in CD40 ¡ tumors, suggesting the potential use of virus for tumor immunotherapy regardless of CD40 status. 6,7,52 This is in accordance with our study in which Ad3-hTERT-CMV-hCD40L (Figs. 3C-E) as well as virally produced hCD40L (Figs.…”
Section: Discussionsupporting
confidence: 92%
“…Unfortunately, adenovirus alone is not potent enough to initiate a powerful vaccine effect thus presenting the rationale for arming them with immunostimulatory molecules such as CD40L, a potent stimulator of dendritic cells (DCs). [4][5][6][7] There are more than 50 identified serotypes of adenoviruses. Serotype 5 adenoviruses (Ad5) are commonly used in gene therapy applications.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Anticancer agents that have been applied via IT injection include chemotherapy agents (eg, vincristine), oncolytic viruses (eg, ONYX-015), immunomodulators (eg, agonistic CD40 monoclonal antibodies), and autologous immune cells (eg, dendritic cells). [2][3][4][5][6][7][8][9] Potential advantages of IT delivery of anticancer drugs include better anticancer effectiveness through achievement of high concentrations of anticancer agents within the tumor microenvironment and reduced systemic adverse drug reactions (ADRs) and drug resistance. 5,[10][11][12] In general, single-agent efficacy has been less than satisfying to date; however, promising results have been achieved using IT-administered targeted therapies, combined with conventional chemotherapy or radiation.…”
Section: Introductionmentioning
confidence: 99%
“…The CD40-CD40 ligand (CD40L) interaction plays an important regulatory role aspects of in DC function such as T-lymphocyte activation and effector cytokine production [9] . Researchers have shown that arming an oncolytic virus with CD40L brings the tumor antigens to the DC surface by CD40L, thereby initiating more effective anti-tumor immunity [10] .…”
Section: Original Articlementioning
confidence: 99%